Pathogenesity of Thai Sacbrood Virus to the Ecotypes of Apis Cerana Indica Fab. in Kerala - Devanesan S (Department of Agricultural Entomology, College of Agriculture, 1998)
Identification of ecotypes of the Indian bee A. cerana indica Fab. in different ecological niche in Kerala adopting statistical analysis of the morphometric data was attempted in the investigation. Sixty worker bees each were collected from 18 locations distributed throughout Kerala and data on 50 selected characters were collected. Univariate analysis showed significant variations in the data with reference to all the fifty characters indicating the desirability of a multivariate analysis for identifying sub groups of A. cerana indica available in the state. A comparison of the honeybee population of the three topographic divisions of the state viz., highrange, highland and midland, with reference to each morphometric character revealed that the bees from highrange were distinct from those of highland and midland. There was less distinction between the bees of the latter two divisions. It also indicated that the highrange bees possessed longer proboscis, antennae, wings and legs. The abdominal size also showed an increasing trend in highland and highrange bees. Eleven morphometric characters were positively correlated with altitude while seven characters showed negative correlation.